Arab Academics’ Perceptions of Fusha and Amiyah in Arabic Language Instruction in Indonesia - Nukman Nukman; Muhammad Mubasysyir Munir; Ahmad Fadhel Syakir Hidayat; Mowafg Masuwd; Noor Zinatul Hamidah (Al-Jawhar : Journal of Arabic Language, 2026)
Arabic language instruction in Indonesian higher education faces the diglossic challenge between Fusha (standard Arabic) and Amiyah (colloquial dialects). Instruction predominantly emphasizes Fusha, while Amiyah is rarely or never formally taught, resulting in students who are proficient in formal literacy but limited in practical communication. This study aims to explore academics’ perceptions regarding the teaching of Fusha and Amiyah, understand students’ challenges, and evaluate the curriculum strategies employed. A descriptive qualitative approach was adopted, involving in-depth interviews with 20 Arabic language academics from various State Islamic Universities (UINs) across Indonesia, analyzed using content analysis techniques. Findings indicate that Fusha serves as the primary foundation for academic literacy, whereas Amiyah is acquired informally through extracurricular experiences or exchange programs. Teaching strategies include lectures, text analysis, discussions, and Fusha-based writing exercises. These results provide an in-depth understanding of the prioritization of formal literacy and underscore the need to develop optional Amiyah modules to equip students with cross-cultural communication skills. The study recommends further exploration of integrating Amiyah into the formal curriculum.